Comparative profiling of canonical and non-canonical small RNAs in the rice blast fungus, Magnaporthe oryzae - Lee, Hyunjun; Choi, Gobong; Lim, You-Jin; Lee, Yong-Hwan (Frontiers in Microbiology, 2022)
RNA interference (RNAi) is divided into canonical, Dicer-dependent and non-canonical, Dicer-independent pathways according to Dicer protein dependency. However, sRNAs processed in a Dicer-independent manner have not been reported in plant pathogenic fungi, including Magnaporthe oryzae. We comparatively profiled the Dicer-dependent and -independent sRNAs of M. oryzae. Dicer-dependent sRNAs were 19-24-nt in length, had low strand-specificity, and showed a preference for uracil at the 5'-end. By contrast, Dicer-independent sRNAs presented irregular patterns in length distribution, high strand-specificity, and a preference for cytosine at the penultimate position. Dicer-dependent sRNA loci were mainly associated with LTR-transposons, while Dicer-independent sRNAs were associated with protein-coding genes and transposons. We identified MoERI-1, a non-canonical RNAi component, and profiled the sRNA and mRNA transcriptomes of ΔMoeri-1 at the mycelia and conidiation stages, as the mutant showed increased conidiation. We found that genes involved in conidiation and cell cycle were upregulated by MoERI-1 deletion. Furthermore, a comparison between sRNA and mRNA transcriptome revealed that MoERI-1-dependent sRNAs mediate the regulation of gene expression. Overall, these results showed that M. oryzae has non-canonical RNAi pathways distinct to the Dicer-dependent manner and exploits MoERI-1-dependent sRNAs to regulate the conidiation process.